Eccentric Exercise Program Design: A Periodization Model for Rehabilitation Applications - Harris-Love, Michael O.; Seamon, Bryant A.; Gonzales, Tomas I.; Hernandez, Haniel J.; Pennington, Donte; Hoover, Brian M. (Frontiers in Physiology, 2017)
The applied use of eccentric muscle actions for physical rehabilitation may utilize the framework of periodization. This approach may facilitate the safe introduction of eccentric exercise and appropriate management of the workload progression. The purpose of this data-driven Hypothesis and Theory paper is to present a periodization model for isokinetic eccentric strengthening of older adults in an outpatient rehabilitation setting. Exemplar and group data are used to describe the initial eccentric exercise prescription, structured familiarization procedures, workload progression algorithm, and feasibility of the exercise regimen. Twenty-four men (61.8 ±6.3 years of age) completed a 12-week isokinetic eccentric strengthening regimen involving the knee extensors. Feasibility and safety of the regimen was evaluated using serial visual analog scale (VAS, 0-10) values for self-reported pain, and examining changes in the magnitude of mean eccentric power as a function of movement velocity. Motor learning associated with the familiarization sessions was characterized through torque-time curve analysis. Total work was analyzed to identify relative training plateaus or diminished exercise capacity during the progressive phase of the macrocycle. Variability in the mean repetition interval decreased from 68% to 12% during the familiarization phase of the macrocycle. The mean VAS values were 2.9 ±2.7 at the start of the regimen and 2.6 ±2.9 following 12 weeks of eccentric strength training. During the progressive phase of the macrocycle, exercise workload increased from 70% of the estimated eccentric peak torque to 141% and total work increased by 185% during this training phase. The slope of the total work performed across the progressive phase of the macrocycle ranged from -5.5 to 29.6, with the lowest slope values occurring during microcycles 8 and 11. Also, mean power generation increased by 25% when eccentric isokinetic velocity increased from 60 deg s-1 to 90 deg s-1 while maintaining the same workload target. The periodization model used in this study for eccentric exercise familiarization and workload progression was feasible and safe to implement within an outpatient rehabilitation setting. Cyclic use of higher eccentric movement velocities, and the addition of active recovery periods, are featured in the proposed theoretical periodization model for isokinetic eccentric strengthening.